The Convergence of Business Process Management and Digital Innovation - Mendling, Jan; Pentland, Brian; Recker, Jan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Business process management is a prolific field of research and an area of strong industrial uptake with roots in both management science and information systems engineering. Traditionally, business process management has largely been utilized in an inward-looking way with the aim to improve operations, eliminate waste, and increase efficiency. Recent developments around digital innovation challenge conventional ideas of process reengineering with a strong emphasis on the external market and exploration. In this talk, we will discuss the complementarity of BPM and digital innovation.